Political regime in post-soviet Kazakhstan: background and features of transformation - Complak, K.; Badanova, M. (KSU publ, 2015)
This article discusses the formation of the political system of modern Kazakhstan after the collapse of the Soviet Union. Also examines the ideological and theoretical aspects of the political modernization process that is still ongoing. An analysis of gradual political transition in Kazakhstan.
Keywords: political system; post-Soviet Kazakhstan; political transformation; Soviet Union